PENGEMBANGAN MODUL ELEKTRONIC MENGGUNAKAN EXE LEARNING PADA MATERI BANGUN DATAR SEGIEMPAT DAN SEGITIGA DI KELAS VII SMPN 3 X KOTO - Zessi Yulida Sari (Departemen Matematika, 2021)
This study aims to develop an e-module with an exe-learning application on quadrilateral and triangular shapes in class VII SMPN 3 X Koto that meet valid and practical criteria. The type of research used is design research type development studies with the ADDIE development model which in its implementation consists of the analysis stage, the design stage, the development stage, and the implementation stage. The research subjects were students of class VII.2 SMPN 3 X Koto. This type of research data is primary data consisting of qualitative and quantitative data. The data obtained were then analyzed using quantitative and qualitative analysis techniques. The results of data analysis show that the developed e-module is valid and practical. Based on the results of the validation and suggestions of the validator, this e-module meets the valid criteria with a validity level of 89.21% (very valid). The results of the student responses in the one-to-one stage to assess the practicality of the e-module have been practical with a practicality level of 93.56% (very practical), while in the small group evaluation stage the practicality level is 78.98% (practical). These results identify that the e-module on the material of quadrilateral and triangular shapes developed in class VII is valid and practical. Keyword – E-module, Exe-learning, Valid, Practical